Pengaruh Substitusi Hay Rumput Kume Dengan Hay Fodder Jagung Hidroponik Terhadap Profil Darah Kambing Kacang - Siyanting Da Conceicao; Gusti A. Y. Lestari; Imanuel Benu; Gustaf Oematan (Yayasan Sumber Daya Manusia Cerdas, 2026)
This study aims to evaluate the effect of kume grass hay substitution with hydroponic mize hay fodder on the blood profile of kacang goats. A total of eight male goats aged 6-8 months with a body weight of 10-15 kg were used in the change over design. Four feed traetmens were used , namaely DMF0 (70% kume grass hay + 30% concentrate), DMF1 (52,5% kume grass hay + 17,5% hydroponic mize hay fodder + 30% concentrate), DMF2 (35% kume grass hay + 35% hydroponic mize hay fodder + 30% concentrate), DMF3 (17,5% kume grass hay + 52,5% hydroponic mize hay fodder + 30% concentrate). The data was analysed using analysis pf variance (ANOVA) with SPSS 25 software. The parameters measured included leukocytes, erythrocytes, haemoglobin, and hematoctir (PCV). The results of the analysis showed that the substitution of kume grass hay with hydroponic mize hay fodder did not have a significant effect on all blood parameters measured (P>0,05). The mean values of leukocytes were 9,612-19,975 g/dl, erythrocytes 12,920-18,773 µm. haemoglobin 6,875-10,125 g/dl, and haematocrit 19,925-30,200%. In conclucion, hydroponic mize hay fodder can be used as a feed alternative without affecting the blood profile of kacang goats, supporting metabolic balanced and livestock health.